River lamprey present an unusual predation threat to Atlantic salmon smolts in Lough Neagh, Northern Ireland. - Kennedy, Richard; Campbell, W.; Gallagher, K.; Evans, Derek W. (Journal of Fish Biology, 2020)
Publication history: Accepted - 28 July 2020; A new monitoring programme on the Lough Neagh catchment has documented a high incidence of river lamprey, Lampetra fluviatilis L., predation on Atlantic salmon smolts, Salmo salar L.,. In total 470 smolts were examined during the 2020 emigration period with 168 fish (36%) exhibiting lamprey scars of which 57 were lightly scarred and 111 were classed as heavily scarred. Lamprey predation was not size selective on Lough Neagh S. salar smolts. This work was funded by Department of Agriculture, Environment and Rural Affairs for N. Ireland.